Enhanced electromagnetic wave absorption of magnetic Co nanoparticles/CNTs/EG porous composites with waterproof, flame-retardant and thermal management functions. Issue 32 (9th August 2021) - Xiang, Zhen; Zhu, Xiaojie; Dong, YanYan; Zhang, Xiang; Shi, Yuyang; Lu, Wei
Abstract : Attributed to rational-designed components and novel nano-micro structures, Co/CNTs/EG porous composites achieved an enhanced electromagnetic wave absorption with favorable waterproof, flame-retardant, and thermal management functions. Abstract : High-performance electromagnetic wave absorbing materials have aroused widespread interest, but their synthesis is still a tremendous challenge. Here, we demonstrated the multifunctional electromagnetic absorbing characteristics of magnetic cobalt nanoparticles suspended in carbon nanotubes/expanded graphite (Co/CNTs/EG) porous composites. The well-designed multi-component and novel nano-micro porous structure endowed Co/CNTs/EG porous composites with an enhanced electromagnetic wave absorption performance. As expected, a high reflection loss of −67.2 dB, an ultrathin thickness of 1.4 mm, a broad effect absorption bandwidth of 5.1 GHz, and an ultra-low filler loading of 3 wt% were achieved. The underlying microwave absorption mechanism was synergistic effects between conduction loss caused by electron transmission in the 3D conductive network, dielectric loss attributed to dipole and interface polarization in the porous structure, magnetic loss originating from the magnetic resonance of Co nanoparticles, and multiple reflections in the porous framework. In addition, the Co/CNTs/EG porous composites exhibited favorable waterproof, flame retardant, thermal insulation, and infrared shielding functions. Therefore, we report a flexible development strategy of novel porous composites with multifunctional and efficient electromagnetic wave absorption performances.